1994
DOI: 10.1063/1.356842
|View full text |Cite
|
Sign up to set email alerts
|

Spin diffusion in classical Heisenberg magnets with uniform, alternating, and random exchange

Abstract: We have carried out an extensive simulation study for the spin autocorrelation function at T=∞ of the one-dimensional classical Heisenberg model with four different types of isotropic bilinear nearest-neighbor coupling: uniform exchange, alternating exchange, and two kinds of random exchange. For the long-time tails of all but one case, the simulation data seem incompatible with the simple ∼t−1/2 leading term predicted by spin diffusion phenomenology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Our main motivation for revisiting the derivation above is recent literature on classical and quantum spin chains with SU(2) symmetry in d = 1 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Section 6). In fact, we were inspired to carry out this effective field theory computation in part by papers arguing that the infinite temperature classical Heisenberg model does not have conventional spin diffusion [16,24,32], as predicted and obtained by many other authors [18,21,30]. In particular, [32] argues that the spin diffusion constant scales as D(t) ∼ log 4/3 t.…”
Section: Introductionmentioning
confidence: 99%
“…Our main motivation for revisiting the derivation above is recent literature on classical and quantum spin chains with SU(2) symmetry in d = 1 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Section 6). In fact, we were inspired to carry out this effective field theory computation in part by papers arguing that the infinite temperature classical Heisenberg model does not have conventional spin diffusion [16,24,32], as predicted and obtained by many other authors [18,21,30]. In particular, [32] argues that the spin diffusion constant scales as D(t) ∼ log 4/3 t.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the classical limit S → +∞, where spin operators in Eq. (3) are replaced by standard unit vectors, identifying whether spin diffusion is normal or anomalous has a long-standing history [51][52][53][54][55][56][57][58]. The issue was settled by doing a systematic finite-size analysis in Ref.…”
mentioning
confidence: 99%
“…Although the phenomenology of spin diffusion is an old concept [3,4], its validity in classical Heisenberg model has been vigourously debated in recent times. Although much effort [13][14][15][16][17][18][19][20] has been devoted to understand whether spin diffusion in this system is normal or anomalous, a convincing conclusion is yet to be reached. Settling this question is not only conceptually important e.g., in understanding transport properties of spin systems, but also has direct implications in routinely performed experiments e.g., NMR and ESR in magnetic compounds [5][6][7][8][9].…”
mentioning
confidence: 99%
“…The authors of Ref. [19] suggested that spin diffusion appears to be diffusive for the alternate coupling case, whereas, for random coupling, it is probably non-diffusive. However, for both the cases we find a clear t −1/2 behavior at late times.…”
mentioning
confidence: 99%
See 1 more Smart Citation